Substitution of aspartic acid with glutamic acid increases the unfolding transition temperature of a protein - Lee, DY; Kim, KA; Yu, YG; Kim, KS (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2004)
Proteins from thermophiles are more stable than those from mesophiles. Several factors have been suggested as causes for this greater stability, but no general rule has been found. The amino acid composition of thermophile proteins indicates that the content of polar amino acids such as Asn, Gln, Ser, and Thr is lower, and that of charged amino acids such as Arg, Glu, and Lys is higher than in mesophile proteins. Among charged amino acids, however, the content of Asp is even lower in thermophile proteins than in mesophile proteins. To investigate the reasons for the lower occurrence of Asp compared to Glu in thermophile proteins, Glu was substituted with Asp in a hyperthermophile protein, MjTRX, and Asp was substituted with Glu in a mesophile protein, ETRX. Each substitution of Glu with Asp decreased the T-m of MjTRX by about 2degreesC, while each substitution of Asp with Glu increased the T-m of ETRX by about 1.5degreesC. The change of T-m destabilizes the MjTRX by 0.55 kcal/mol and stabilizes the ETRX by 0.45 kcal/mol in free energy. (C) 2004 Elsevier Inc. All rights reserved.